2009
DOI: 10.1111/j.1530-0277.2008.00838.x
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Consequences of Repeated Nicotine During Adolescence in Alcohol‐Preferring AA and Alcohol‐Avoiding ANA Rats

Abstract: These findings provide no or little support for the views that adolescent animals are more sensitive to the neurobehavioral effects of repeated exposure to nicotine and that exposure to nicotine in adolescence may contribute to enhanced vulnerability to ethanol abuse. Furthermore, genetic predisposition to high or low ethanol self-administration does not seem to be a factor that influences individual vulnerability to the neurobehavioral effects of repeated administration of nicotine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 57 publications
2
14
0
Order By: Relevance
“…For example, Tsui et al (2001) demonstrated that nicotine during adolescence, using a similar preexposure preparation as the present study, enhanced the acquisition of alcohol consumption in adulthood. However, other studies have demonstrated that continuous nicotine delivered via mini-osmotic pumps during periadolescence does not alter voluntary alcohol consumption immediately subsequent to nicotine exposure (Smith et al , 2002), nor does nicotine preexposure during periadolescence alter alcohol consumption in alcohol-preferring (AA) rats (Kemppainen et al , 2009). Parametric differences (e.g., length of nicotine preexposure, dose of nicotine, route of administration, strain of rat) preclude any conclusions regarding the influence of alterations in the aversive effects of alcohol after periadolescent nicotine preexposure on alcohol consumption.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Tsui et al (2001) demonstrated that nicotine during adolescence, using a similar preexposure preparation as the present study, enhanced the acquisition of alcohol consumption in adulthood. However, other studies have demonstrated that continuous nicotine delivered via mini-osmotic pumps during periadolescence does not alter voluntary alcohol consumption immediately subsequent to nicotine exposure (Smith et al , 2002), nor does nicotine preexposure during periadolescence alter alcohol consumption in alcohol-preferring (AA) rats (Kemppainen et al , 2009). Parametric differences (e.g., length of nicotine preexposure, dose of nicotine, route of administration, strain of rat) preclude any conclusions regarding the influence of alterations in the aversive effects of alcohol after periadolescent nicotine preexposure on alcohol consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our results, Kemppainen et al . 37 found no effect of adolescent nicotine pre-exposure on subsequent alcohol intake in adulthood. However, a challenge of nicotine given to rats with a history of nicotine exposure increased alcohol self-administration compared to nicotine-naïve controls 37 , suggesting that nicotine pre-treatment leads to sensitizing effects relevant to alcohol intake.…”
Section: Discussionmentioning
confidence: 69%
“…While several studies have shown that nicotine treatment acutely increases alcohol intake (e.g., refs 11, 12, 16 and 17) and alcohol relapse 12, 17 , only a few studies tested the effects of a repeated nicotine treatment on subsequent alcohol self-administration (e.g., refs 10 and 37). Similar to our results, Kemppainen et al .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, [23] observed that female adolescent mice (PND 35-41) exposed to nicotine showed increased bottle-drinking ethanol consumption on (PND [41][42][43][44]. The effects of nicotine exposure during adolescence on ethanol intake seem to depend on the treatment age, duration, strain, sex, and nicotine withdrawal period [23,40]. To our knowledge, this is the first study that has demonstrated increased operant saccharine self-administration while assessing the consequences of nicotine pretreatment during adolescence in later life.…”
Section: Discussionmentioning
confidence: 92%